Racial differences in treatment adherence and response to acupuncture and cognitive behavioral therapy for insomnia among Black and White cancer survivors - Kevin T. Liou; Sheila N. Garland; Salimah H. Meghani; Nadia M. Kaye; Embree Thompson; Q. Susan Li; Jun J. Mao (Cancer Medicine)
Abstract Background Racial disparities in sleep are well‐documented. However, evidence‐based options for addressing these disparities are lacking in cancer populations. To inform future research on sleep interventions, this study aims to understand racial differences in treatment responses to acupuncture and cognitive behavioral therapy for insomnia (CBT‐I) among Black and White cancer survivors. Methods We conducted a secondary analysis of a comparative effectiveness trial evaluating acupuncture versus CBT‐I for insomnia in cancer survivors. We compared insomnia severity, sleep characteristics, and co‐morbid symptoms, as well as treatment attitudes, adherence, and responses among Black and White participants. Results Among 156 cancer survivors (28% Black), Black survivors reported poorer sleep quality, longer sleep onset latency, and higher pain at baseline, compared to White survivors (all p < 0.05). Black survivors demonstrated lower adherence to CBT‐I than White survivors (61.5% vs. 88.5%, p = 0.006), but their treatment response to CBT‐I was similar to white survivors. Black survivors had similar adherence to acupuncture as white survivors (82.3% vs. 93.4%, p = 0.16), but they had greater reduction in insomnia severity with acupuncture (−3.0 points, 95% CI −5.4 to 0.4, p = 0.02). Conclusion This study identified racial differences in sleep characteristics, as well as treatment adherence and responses to CBT‐I and acupuncture. To address racial disparities in sleep health, future research should focus on improving CBT‐I adherence and confirming the effectiveness of acupuncture in Black cancer survivors.